Former des retraités au tutorat : questionner les incidents critiques pour conceptualiser les compétences transversales liées à l’action - Laurence Durat (Recherches en Éducation)
Requested to shed light on the question of the transferability of the senior experience in a student tutoring system, we hypothesized that a path could be to question critical incidents of these experienced professionals in order to help formalize the processes at work in the development of their transversal skills. The return to a lived situation described in (filmed) narratives, reworked collectively with their peers, has indeed made it possible to reveal the perceptive structure of the experience by showing the cognitive, conative and socio-emotional elements that make up the development of transversal skills.